Divestment discourse: war, justice, morality and money. Issue 2 (4th March 2018) - Mangat, Rupinder; Dalby, Simon; Paterson, Matthew
ABSTRACT: The fossil fuel divestment movement has been a vibrant novel development in climate change politics in recent years, particularly in North America. Here, the character of the discourse used to promote divestment as a strategy is explored. The divestment discourse is shown to rest on four overlapping narratives, those of war and enemies, morality, economics and justice. All four are clearly discernible in statements from movement activists, in coverage of divestment campaigns by major news sources and in the movement's aims, objectives and strategies covered in alternative media. The war narrative, with the formulation of fossil fuel companies as enemies to be overcome to ensure survival, is the dominant narrative. By polarising climate action and identifying an antagonist against which to mobilise, divestment discourse has articulated climate change as an explicitly political phenomenon, in contrast to the primarily consensus and collaboration-based approaches that have predominated in climate politics.